Strategy of the Financial Services Authority in Developing Digital Talent Competence in the Financial Technology Era in the Banking Sector - Lia Kusumawati; Eko Prasojo (Department of Public Administration, 2023)
Digital talent competency is an urgent to fulfill the digital competency requirements need in the labour industry. The World Economic Forum report in 2018 estimated that nearly 75 million jobs will be lost as a result of Artificial Intelligence technology development in 2025, but it is also estimated that nearly 133 million new jobs will be created. This makes the gap in competency requirements for digital talent in the banking sector unavoidable in the digitalisation of the economy. The Banking Industry requires competent human resources in order to improve the quality and variety of financial services products based on digital technology. The purpose of this article is to determine OJK's strategy in developing human resources in the banking industry, which is one of the important factors to improve competence and understanding of financial services products, so as to provide services that prioritise consumer protection and productivity. This research uses descriptive qualitative methods through literature studies, observations and interviews. The results show that efforts to fulfill the competency gap require planned, measurable, and sustainable human resource development by preparing the Indonesian National Work Competency Standards, preparing the Indonesian National Qualifications Framework, increasing human resource development through training, seminars, and workshops and fulfilling competency needs in the field of digital technology through the preparation of the Digital Competency Dictionary